Etatyzacja gospodarki w okresie rządów komunistycznych w Polsce - Kaliński, Janusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
In the years between 1944–1955 lasting foundations of the Polish economy were created based on communist dogma. In the mid-1950 s the so called socialized sector provided 75% of national income, however, multidirectional changes in economic policy in the following decades caused fluctuations in its importance. The changes were expressed by increases and decreases in the private sector share of jobs. As a result, the socialized sector was at its the peak in the 1970 s (86% share of the socialized sector in national income) only to fall to 81% of national income in the last year of communist rule. The dominance of the public sector was responsible for widespread mismanagement and social pathologies which led to the collapse of the economically inefficient system, preceded by a number of socio-political crises